Padrões de distribuição espacial e temporal em comunidades de ácaros em seringueira (Hevea SPP.) no Brasil - Nuvoloni, Felipe Micali [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The rubber tree, Hevea brasiliensis (Muell. Arg. Euphorbiaceae) is the main source of natural rubber in the world, being originated and constrained to the Amazon basin. In the last years, the study of species of mites associated with rubber crop have been focused due to the importance of Calacarus heveae Feres, and Tenuipalpus heveae Baker, which occasionally induce severe defoliation and losses on latex production. Although, most of studies has highlighted local results, being absent broadscale studies, and connected data analysis. We performed a compilation of literature data, and complemented it with field sampling, aiming to diminish the lack of knowledge about the mites associated with rubber trees in Brazil. Our results highlight the huge diversity of species (250) recorded on rubber trees, from which C. heveae, T. heveae and Phyllocoptruta seringueirae Feres were the most abundant. These species present a populational peak comprised between February to May. Native rubber trees from Amazon also can harbor a great diversity of Phytoseiidae species, since seven new species were described from there. Beyond that, based on the communities temporal dynamics, we verified that regardless of the locality, all the communities of mites follow the same strict patter of species accumulation through time. In this sense, the traditional approach, that relies on the species-time-relationship STR could not be applied to our data. As a result, we built a new approach based on the turnover rates, disentangling the Colonization and Extinction components from turnover metric (Sorensen). At least, the spatial structure of the communities was driven by the dispersion-based component, and in the environmental component autocorrelated with space, in a biogeographic scale. On the other hand, the effect of these components also changed according to the taxon. At least, number of species was also negatively modeled ...

A seringueira, Hevea brasiliensis (Muell. Arg. Euphorbiaceae) é a principal fonte de borracha natural do mundo, e tem como centro de origem e ocorrência natural a região Amazônica. Nos últimos anos o estudo da acarofauna associada à heveicultura tem ganhado destaque, principalmente devido aos danos e perdas econômicas ocasionados por Calacarus heveae Feres, e Tenuipalpus heveae Baker. Entretanto, a maioria dos resultados obtidos refletem particularidades locais, não havendo análise de dados em grande escala e em conjunto. Dessa forma, realizamos a integração dos dados de literatura com incursões a campo visando preencher lacunas no conhecimento da acarofauna associada a seringueiras no Brasil. Nossos resultados enfatizam a elevada diversidade de espécies (250) registradas em seringueiras, sendo C. heveae, T. heveae, e Phyllocoptruta seringueirae Feres, as mais abundantes. Estas espécies tiveram seus picos populacionais compreendidos entre os meses de fevereiro e maio. As seringueiras nativas da Amazônia podem abrigam uma enorme diversidade de ácaros Phytoseiidae, visto que sete novas espécies foram descritas a partir desta região. Além disso, baseando-se nos estudos de dinâmica temporal das comunidades, verificamos que independentemente da localização geográfica, as comunidades exibem um mesmo padrão de acumulação temporal de espécies, e a abordagem tradicional (species-time-relationship, STR) não pode ser aplicada ao nosso sistema de estudo. Dessa forma, elaboramos uma nova abordagem baseada na taxa de turnover temporal, a partir do desmembramento dos componentes de Colonização e Extinção da métrica de turnover (Sorensen). Por fim, considerando-se a estruturação das comunidades no espaço, os processos baseados na dispersão das espécies, e o componente ambiental autocorrelacionado com o espaço, são os principais fatores determinando a montagem das comunidades em...
Keywords: Ecologia; Acarologia; Ácaro de plantas; Seringueira - Brasil; Biodiversidade